UTILIZATION OF SARDINES - MADHAVAN, P.; NAIR, T. S. UNNIKRISHNAN (Fishery Technology, 2016)
Oil sardine Sardinella longiceps stands out as the single largest pelagic fishery in India contributing to about 30% of total marine fish landings. Commensurate with the volume of the fishery, efforts at proper utilization of the fish by processing into canned and frozen products or by distributing in fresh state to internal consuming centres by quick transport have remained rather very poor. The paper presents the problems and prospects with regard to the utilization of the fish on the above lines. Results of investigations made at CÂ· I. F. T. on the utilization of sardine body oil into industrially useful products such as factice, vehicle for paints, additive in lubricating oil and base for printing ink have also been discussed.